Alumni commitment in higher education institutions: determinants and empirical evidence - Pedro, Ilda Maria H. (2020)
This paper intends to analyze alumni commitment as a determinant to loyalty, measured by recommendation and participation and to identify its determinants considering satisfaction and image variables. Using data of a public Portuguese higher education institution, the results suggest that the performance and the timetable of support services, as well as the relationship with teachers, are determinants of alumni recommendation, whereas a good opinion of the quality of educational training, the satisfaction with the teachers’ ability, the relationships with them and with the non-academic staff strength the alumni participation in the institution’s activities. Although both satisfaction and image variables are determinant to explain alumni loyalty, their effects on loyalty seem to be unbalanced as the image variables seem to be more determinant in increasing both the probability of recommendation and participation. These results provide relevant information to support communication and advertising strategies and they may be a good help to other Higher Education Institutions.